Preclinical stress originates in the rat optic nerve head during development of autoimmune optic neuritis - Stojic, Aleksandar; Bojcevski, Jovana; Williams-Fairless, Sarah K.; Bas Orth, Carlos; Diem, Ricarda; Fairless, Richard (Glia, 2019)
Optic neuritis is a common manifestation of multiple sclerosis, an inflammatory demyelinating disease of the CNS. Although it is the presenting symptom in many cases, the initial events are currently unknown. However, in the earliest stages of autoimmune optic neuritis in rats, pathological changes are already apparent such as microglial activation and disturbances in myelin ultrastructure of the optic nerves. αB-crystallin is a heat-shock protein induced in cells undergoing cellular stress and has been reported to be up-regulated in both multiple sclerosis and its animal model, experimental autoimmune encephalomyelitis. Therefore, we wished to investigate the timing and localization of its expression in autoimmune optic neuritis. Although loss of oligodendrocytes was not observed until the later disease stages accompanying immune cell infiltration and demyelination, an increase in oligodendrocyte αB-crystallin was observed during the preclinical stages. This was most pronounced within the optic nerve head and was associated with areas of IgG deposition. Since treatment of isolated oligodendrocytes with sera from myelin oligodendrocyte glycoprotein (MOG)-immunized animals induced an increase in αB-crystallin expression, as did passive transfer of sera from MOG-immunized animals to unimmunized recipients, we propose that the partially permeable blood-brain barrier of the optic nerve head may present an opportunity for blood-borne components such as anti-MOG antibodies to come into contact with oligodendrocytes as one of the earliest events in disease development.
First published: 21 December 2018
Gesehen am 02.09.2019